Pengembangan Media Games Education dalam Pembelajaran Matematika - Fajar Khoirul Fahmi (Universitas Indraprasta PGRI, 2016)
The aim of this research is to develop media games education in learning mathematics. The research was conducted to fourth grade of State Elementary School Meruya Utara 02 Pagi. Research model used ADDIE instructional model. In this research, media product has been tested by an expert of media, two expert of mathematics and an expert of instructional design. From the trial, the mean value from the formative evaluation of an expert of instructional design was 4.50, the mean value from the formative evaluation of the first expert material was 4.60, the mean value from the formative evaluation of the second expert material was 4.65 and the mean value from the formative evaluation of an expert of instructional design was 4.55. From all of the trial result, media games education in learning mathematics for the fourth grade of Elementary School is good. This is proven that media games education successfully improve the students’ mathematics achievement, and more effective in learning process at school, especially in learning multiplication for mathematics subject.